(untitled) - Root, Michael (New York, 2011)
Supercharge your understanding of battery technologyIdeal for hobbyists and engineers alike, The TAB Battery Book: An In-Depth Guide to Construction Design and Use offers comprehensive coverage of these portable energy powerhouses. This practical guide discusses battery chemistry and engineering, how batteries are used, and the history of batteries. You'll find out how different types of batteries work and how to select the right battery for any application. The book also examines the technological advances being used to develop batteries as robust energy sources for a wide variety of devices. Tap into the power of all kinds of batteries with help from this detailed resource.Coverage includes: portable energy and long-term energy storage Batteries for portable consumer demands, medical devices, electric vehicles, large-scale electrical energy storage, and space and military applications Basic physics and chemistry The science of batteries--cells, electrochemistry, thermodynamics, kinetics, and capacity Battery engineering designs, including electrode, seal, and vent design Battery performance, reliability, and safety Primary battery technologies--aqueous and non-aqueous electrolytes, including alkaline and lithium Rechargeable batteries, including nickel-metal hydride and lithium ion Selecting the right battery for any application Future technologies, such as thin-film, large-energy storage, and high-energy density batteries
Keywords: Electric batteries,Pin điện